1996
DOI: 10.1074/jbc.271.28.16451
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Phospholipase δ1 Is the Effector in the Gh (Transglutaminase II)-mediated Signaling

Abstract: A new class of GTP-binding protein transglutaminase II (G h ) couples to a 69-kDa phospholipase C (PLC). An 8-amino acid region (Leu 665 -Lys 672 ) of the ␣-subunit of G h (G␣ h ) is involved in interaction and activation of PLC, an observation that has now been used to characterize the 69-kDa PLC further. A 20-amino acid peptide corresponding to Leu 654 -Leu 673 of G␣ h was used to prepare an affinity resin. On incubation with a partially purified PLC preparation from rat liver membranes, the affinity resin-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
163
3
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(173 citation statements)
references
References 27 publications
6
163
3
1
Order By: Relevance
“…Tissue transglutaminase has been proposed to be implicated in a vast array of cellular processes, including the suppression of cell proliferation, differentiation, and signal transduction (30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue transglutaminase has been proposed to be implicated in a vast array of cellular processes, including the suppression of cell proliferation, differentiation, and signal transduction (30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…GTP-bound TGase participates in signaling pathways that link cell surface receptors to intracellular effectors. The most studied example of this involved the up-regulation of phospholipase C activity by the ␣ 1 -adrenergic receptor (13,14), where it was shown that the ␣ 1 -adrenergic receptor stimulated the GTP binding activity of TGase. The GTP-bound TGase species, in turn, was shown to stimulate phosphoinositide lipid hydrolysis by phospholipase C. The ability of TGase to transduce signals adds another dimension to its functionality and may help explain how the same protein can be linked to several, sometimes opposing, cellular responses.…”
mentioning
confidence: 99%
“…PLC-␥s are regulated by receptor or nonreceptor protein-tyrosine kinases and PIP 3 (4). PLC-␦s are regulated by a GTP-binding protein transglutaminase (7). PLC-␦s are also more sensitive to Ca 2ϩ than the other isozymes and, unlike PLC-␥s and PLC-␤s, are activated by Ca 2ϩ alone (8).…”
mentioning
confidence: 99%